INCREASE IN FLUID EXTRACTION, WHICH IS AT THE FINAL STAGE OF DEVELOPMENT DUE TO THE IMPROVEMENT OF EQUIPMENT INTENSIFICATION (Academic journal Industrial Machine Building Civil Engineering, 2019)
It has been established that the fluid reserves, which are at the final stage of development, are difficult to extractable andwatered. The methods of intensification are analyzed and it is established that it will be rational in this case to pump carbondioxide into the reservoir. Its influence on a bundle of oil and water is determined. The results of the statistical processing ofthe change of the debit before and after injection of carbon dioxide, the influence of the volume of gas injected into the wellfrom the seperate permeability of the reservoir, as well as the expected rate of wellbore after injection, are presented.
Keywords: buffer tanks for carbon dioxide; carbon dioxide; fluid; gas well; injection wells; productive layer; pump station; viscous oil sand; water content